Improving Student Learning Outcomes Through Video Aided Problem Based Learning Model - Ria Titis Pratiwi (Universitas Sebelas Maret, 2020)
This study aims to improve the learning outcomes of the third grade students of SD Negeri 05 Bantarbolang on the sub-theme of Aneka Benda around me through a video-assisted problem-based learning model. This research is a Classroom Action Research (PTK) which consists of three cycles, where each cycle is carried out in one face-to-face. The Action Plan for each cycle in the CAR is divided into four activities, namely Planning, Implementation, Observation, and Reflection. The data collection technique in this study is a formative test. The instrument used to collect data was a learning outcome test. Completeness of student learning outcomes in cycle I only reached 60% with a mean of 77, in cycle II student learning completeness reached 87% with a mean of 81, and in cycle III student learning completeness reached 87% with a mean of 83. The results of this study indicate that the application of the learning model video-assisted problem-based learning can improve student learning outcomes.